STRATEGI PENGEMBANGAN PEMBELAJARAN BERDIFERENSIASI (WORKSHOP KURIKULUM MERDEKA GURU-GURU MTSN 10 NGANJUK) - Pitoyo, Andri; Rahmayantis, Marista Dwi; Waryanti, Endang; Sasongko, Sempu Dwi; Sujarwoko; Muarifin, Moch.; Lailiyah, Nur; Puspitoningrum, Encil; Kusmiaji, Ingghar Ghupti Nadia; Putra, Chelya Ilham Ramdani; Firmansyah, Achmad Fathoni (Jurnal Pengabdian Masyarakat Indonesia, 2024)
The service team of the Indonesian language and literature education study programme at Nusantara PGRI Kediri University held a workshop on differentiated learning strategies for teachers at MTSN 10 Nganjuk Regency on 10-12 September 2024. The workshop aims to explain the essence of differentiated learning strategies and develop systematic lesson plans, which are based on legal frameworks such as the National Education System Law and Government Regulations on National Education Standards. Curriculum development paradigms include progressivism, constructivism, humanism and cybernetics, with a focus on fostering students' independence and preparing them for the challenges of the 21st century. Differentiated learning will involve modifying materials, processes, products, environments, and evaluations, while also emphasising the importance of understanding students' learning styles for a more effective learning experience. Thus learning difficulties and other learning problems experienced by students can be resolved and the learning objectives that have been planned by teachers and institutions can be achieved well.